2015
DOI: 10.17269/cjph.106.4667
|View full text |Cite
|
Sign up to set email alerts
|

The association between the interpregnancy interval and autism spectrum disorder in a Canadian cohort

Abstract: OBJECTIVES: Two studies reported an increased risk of autistic disorder in children conceived less than 12 months after a previous birth. Our objective was to examine the association between the interpregnancy interval (IPI) and autism spectrum disorder (ASD) in a Canadian cohort.METHODS: Using administrative datasets housed at the Manitoba Centre for Health Policy, we identified pairs of first-and second-born singleton siblings born between 1988 and 2005. Diagnoses of ASD were ascertained by searching physici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
2
10
1
Order By: Relevance
“…The remaining study reported a nonsignificant greater risk of ASD among children born after an IPI of <12 months (adjusted OR 1.72, 95% CI 0.96-3.06). 32 However, a sensitivity analysis restricted to individuals with more severe ASD revealed a significant association between IPIs of <12 months and this disorder. Three studies also found a significant association between ASD and long IPIs (≥60 months, 31 ≥72 months, 34 and ≥84 months 33 ).…”
Section: Autism Spectrum Disordermentioning
confidence: 95%
See 2 more Smart Citations
“…The remaining study reported a nonsignificant greater risk of ASD among children born after an IPI of <12 months (adjusted OR 1.72, 95% CI 0.96-3.06). 32 However, a sensitivity analysis restricted to individuals with more severe ASD revealed a significant association between IPIs of <12 months and this disorder. Three studies also found a significant association between ASD and long IPIs (≥60 months, 31 ≥72 months, 34 and ≥84 months 33 ).…”
Section: Autism Spectrum Disordermentioning
confidence: 95%
“…A total of 12 studies (6 cohort, 5 cross-sectional, and 1 case-control), including 1 334 569 children, met the inclusion criteria. [28][29][30][31][32][33][34][35][36][37][38][39] The individual characteristics and main findings of the studies included in the systematic review are shown in Table 1. Seven studies provided data on ASD, 28 …”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As recently systematically reviewed, a short IPI has been consistently associated with ASD, conferring about 2‐fold higher risk for children born after an IPI less than 12 months compared with those born after 36 or more months [Cheslack‐Postava, Liu, & Bearman, ; Cheslack‐Postava et al, ; Conde‐Agudelo, Rosas‐Bermudez, & Norton, ; Coo et al, ; Durkin, DuBois, & Maenner, ; Gunnes et al, ; Zerbo, Yoshida, Gunderson, Dorward, & Croen, ]. Short IPI may indicate maternal depletion of nutrients, such as folate, as essential nutrients are preferentially distributed to the developing fetus during pregnancy, and can remain low for up to a year postpartum [O'Rourke, Redlinger, & Waller, ; Smits & Essed ; van Eijsden, Smits, van der Wal, & Bonsel, ].…”
Section: Etiologic Research On Environmental Contributions To Asd: a mentioning
confidence: 99%
“…Some evidence for dose-response, however three studies also showed higher risk with longer intervals. Associations could result from maternal nutrient depletion or cultural, family planning, or lifestyle factors.Cheslak-Postava et al[2011];Dodds et al [2011];Gunnes et al [2013];Cheslack- Postava et al [2014];Coo et al [2015];Durkin et al [2015];Zerbo et al [2015]; Conde-Agudelo et al[2016]…”
mentioning
confidence: 99%